Analysis of Personal Data Protection Implementation on Shopee Online Shopping Application - Rico Ardi Wijaya; Mochammad Tanzil Multazam (Athena: Journal of Social, Culture and Society, 2025)
Online shopping applications are the choice of many people to fulfill their needs. One of the leading online shopping platforms today is shopee. However, with the increasing use of online shopping applications, there are concerns about the security of users' personal data. The purpose of this research is to find out the implementation of personal data protection on shopee online. By using normative juridical method with legislation approach (Statue Approach). The results of this study In the analysis of the implementation of personal data protection in Shopee's Privacy Policy currently does not fully meet the requirements of Law 27 of 2022 concerning Personal Data Protection. There are deficiencies in terms of providing sufficient information to consumers/users about Shopee's identity, legal basis, purpose of processing personal data, and responsibilities.